Mandarin Stroke Social Network Scale and Item Response Theory - Feng, Chun; Lai, Qing-Ling; Ferland, Amanda; Lin, Feng (Frontiers in Stroke, 2022)
Background Stroke survivors may have difficulty in social integration due to physical or mental disorders across the entire continuum of disease. Higher perceived social support can promote social participation for persons following a stroke. However, no scale is available to investigate the perceived social support among the Chinese post-stroke population. Objectives The current study addresses this gap by developing the Mandarin version of the Stroke Social Network Scale (M-SSNS) and examining the reliability and validity of this scale. This study also utilizes the Item Response Theory (IRT) model as a bridge between social ability and functional status. Methods The convenience sampling method was followed to recruit 71 inpatient post-stroke individuals. All participants were evaluated by the modified Barthel Index (MBI), M-SSNS, and the Extended International Classification of Functioning, Disability, and Health (ICF) Core Set for Stroke. The reliability of M-SSNS was explored based on the IRT model. The validity of the scale was further confirmed by assessing the correlation between estimated personal social competence and the final score of the 19-item M-SSNS, and the correlation between estimated personal social competence and functional status based on the ICF. Results A total of 71 patients with stroke (53 males and 18 females) were included in this research. Fourteen items of M-SSNS were selected to represent personal social ability according to the unidimensional 3-parameter logistic (3PL) IRT model. The Cronbach's α of the 14-item scale was 0.7192, with the Guttman's λ2 = 0.7567, Molenaar Sijtsma ρ = 0.7491, and latent class reliability coefficient = 0.8657, indicating that the M-SSNS had great internal consistency. The estimated individual social competence by the 14-item 3PL model was highly related to the final score of the 19-item M-SSNA (p < 0.001, r = 0.79). The correlation between the personal functional status and social ability was 0.23 (p = 0.049, r = 0.23). Conclusion The 14-item M-SSNS manifests great reliability and acceptable validity. Based on the IRT, the 14-item M-SSNS is also a promising tool to assess the social structure and provide customized relationship consulting, education, and advice among the Chinese stroke population.